An Empirical Study of the Factors affecting the Willingness to Pay for Air Pollution Reduction in Zimmerman - Gathogo, Mugo Daniel; Mutsembi, Mr. Manundu; Dr. Wafula, Masai (International Journal of Environmental Sciences, 2016)
Purpose: The purpose of this study was to estimate empirically the effects of the identified factors on the willingness to pay for air pollution reduction. Methodology: System random sampling was used to select the study sample. The sample size was limited to 150 households. Ordinary least squares technique was applied in the data analysis to estimate the effects of the identified factors on the willingness to pay for air pollution reduction. Results: The study results showed that income, education and ranking of the air pollution compared to other problems were significant determinants of willingness to pay for reduction in air pollution problem compared to other problems had the expected signs and were significant at 95% level. The other variable age, family size, marital status and incidence of air pollution related illness had the expected signs, but were not significant at the 95% level as the t-values fell below the critical value of 1.96. Unique contribution to theory, practice and policy: The study recommended0.3 that increasing the income of the individuals may lead to an increase in the charges for air pollution abatement. Educating the people about the virtues of a pollution free environment may increase their willingness to pay for air pollution reduction via payment vehicle such as taxes and service charges or higher prices. The government can help reduce the housing problem by solving the air pollution problem which will further encourage investments in residential housing units in the undeveloped parts of Zimmerman given that it is an important residential estate for the lower middle class to the upper middle class groups as evidenced from the income data gathered.